2005
DOI: 10.1523/jneurosci.0810-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Potent Spinal Analgesia Elicited through Stimulation of NTS2 Neurotensin Receptors

Abstract: Intrathecal administration of the neuropeptide neurotensin (NT) was shown previously to exert antinociceptive effects in a variety of acute spinal pain paradigms including hotplate, tail-flick, and writhing tests. In the present study, we sought to determine whether some of these antinociceptive effects might be elicited via stimulation of low-affinity NTS2 receptors. We first established, using immunoblotting and immunohistochemical techniques, that NTS2 receptors were extensively associated with putative spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
84
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 55 publications
6
84
0
3
Order By: Relevance
“…NT does not induce analgesia because of its poor BBB penetration. As previously reported (40), NT increased the nociceptive threshold in the tailflick test ( Figure 5A). Likewise, i.t.…”
Section: In Vivo Brain Penetration and Plasma Stability Of Ang2002supporting
confidence: 90%
“…NT does not induce analgesia because of its poor BBB penetration. As previously reported (40), NT increased the nociceptive threshold in the tailflick test ( Figure 5A). Likewise, i.t.…”
Section: In Vivo Brain Penetration and Plasma Stability Of Ang2002supporting
confidence: 90%
“…Inward currents in response to NT were also found in guineapig dorsal root ganglia (Kawarada et al, 2000). In situ hybridization revealed expression of NTR1 mainly in small sensory neurons of rat dorsal root ganglia (Zhang et al, 1995), and immunofluorescence analysis revealed the expression of NTR2 in both small and large cells (Sarret et al, 2005). We also confirmed by immunohistochemistry NTR1 expression in sensory ganglion cells, and nuclear NTR1 location supports internalization, also in this structure.…”
Section: Discussionsupporting
confidence: 73%
“…In the brain, NT modulates dopaminergic transmission in the nigrostriatal and mesocortilimbic pathways as well as hormone secretion from the anterior pituitary (Vincent et al 1999). It also exerts potent hypothermic and analgesic effects (Sarret et al 2005). In the periphery, NT is synthesized and secreted by endocrine-like N cells predominantly in the small intestine (Reinecke 1985).…”
Section: Introductionmentioning
confidence: 99%